Anti-Aging Accelerators - A study on the effects of GPU degradation in AI applications - Forssén, Björn (My University, 2026)
By using a model based on first principles, it is possible to argue about the sustainability effects of aging AI accelerator hardware by relaxing some constraints. But first order principles have its limits and despite this effort to reason regarding the replacement of AI accelerator hardware and significant remains to be explored. This work presents some common considerations for reasoning about sustainability with computer hardware, some of the considerations being based on current trends are based on the situation at the time of writing. Then a model based on first principles is explained and is used to reason about replacement of AI accelerator hardware, this is combined with software simulation of faulty hardware in-place of faulty hardware. Finally, we present some of the considerations learned from testing the first-order model and conclude on some suggestions for further work to study the sustainability of AI accelerators.
Keywords: Computer; science; computer science; engineering; project; thesis; DNN; reliability; carbon footprint; sustainability